Beberapa variabel yang mempengaruhi penerimaan pajak daerah di kabupaten malinau (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
The purpose of this study is to analyze and determine the influence of the taxpayer, the taxpayer awareness, Intensification, billing costs and trade, hotels and restaurants sector local tax revenues in Malinau. The analysis in this study uses Multiple Linear Regression Analysis to answer the research problems. The data used is secondary data in the period 2004 to 2013. The study concluded that:The results showed that the taxpayer, the cost of collection and trade, hotels and restaurants sector significantly influence the acceptance of Local Tax in Malinau. Mandatory awareness and intensification of direct taxes not significant effect on tax revenue of Regions in Malinau